Community and the choral program: nurturing lifelong, independent musicians in vocal ensembles - Brown, Christopher (Kansas State University, 2021)
In this report, I will describe my journey towards providing my students with more autonomy in the choral rehearsal. I provide evidence of student autonomy as they improvise, select literature, and travel on the path to independence. Because of the specific restrictions put on music classes during the 2020-2021 school year, I discovered that my singers needed an opportunity to take back control in one way or another. In doing this, it is my personal goal to allow freer conversations and experimentations to be the norm, not the exception, in my ensembles. Much of this change in my thought process has come from examining my own teaching philosophy and the expectations of a singer that has graduated through my program. By attending Kansas State University, I have been privileged to broaden my sense of what it means to be a music educator. Although having previously thought of myself as a well- rounded educator, my experiences in this program have shaped me into finally realizing that goal. Entering this program with the desire to be a better music educator now sees me leaving the program as a better human for all students and teachers that I encounter. The connection that I found in my professors and colleagues is one that I now hope to instill into my program and subsequent students. The absence of these experiences during the COVID-19 pandemic has shifted the way that I view my role in music education. The past year has taught me, if nothing else, that music is a communal activity desired by all. Whether performing, attending, or working behind the scenes, all aspects of the musical experience seek to tighten the bond between its participants.
Keywords: Choir; Team building; Community; Independent musician; Improvisation; Vocal ensemble